Analisis Perbedaaan Tingkat Kinerja Keuangan pada Bank Konvensional dan Bank Syariah di Indonesia - Hendarwati, Atik (Akmenika, 2013)
This paper attempts to analyze the financial performance of Conventional Banks and Islamic Banks in Indonesia. The study is based on secondary data covering the period from 2008 until 2011. Financial ratios includes Capital Adequacy Ratio (CAR), Rasio Efisiensi Operasional (REO) or Biaya Operasional Pendapatan Operasional (BOPO), Non Performing Financing (NPF) or Non Performing Loan (NPL), Financing to Deposit Ratio (FDR) or Loan to Deposit Ratio (LDR) and Return on Assets (ROA). The sampling technique used purposive sampling method. Six bank samples are two conventional banks (Bank BNI dan Bank BTN)and four Islamic banks (Bank Muamalat, Bank Syariah Mandiri, Bank BRI Syariah and Bank Mega Syariah). Independent Samples t-Test used to analyze the financial performance comparison between them. The result of study shows that there are no significant differences in the level of financial performance (which is proxied by the variable ratio of CAR, NPF or NPL, REO or BOPO, FDR or LDR and ROA) between Conventional Banks and Islamic Banks.